Neñcai aḷḷum Cilampu - Caṇmukam, Irāma, 1933- (Maturai Kāmarācar Palkalaik Kaḻaka Añcalvaḻit Toṭarkalvit Tamiḻt Tuṟai veḷiyīṭu, 1983)
Transcript of papers presented at the Seminar on Cilappatikaram, organized by the Institute of Correspondence Course and Continuing Education, Madurai Kamaraj University, 1977-78.